IMPLICATIONS OF THE IMPLEMENTATION OF SYARIAH LAW IN CYBERSPACE IN MALAYSIA - Rosyad, Ali Miftakhu; Mahmoor, Siti Fatahiyah; Sukardi, Didi (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2025)
The rapid advancement of information and communication technology (ICT) has created new legal challenges in cyberspace, particularly within Malaysia’s dual legal system of civil and Syariah law. This study examines the implementation of Syariah law in cyberspace by focusing on jurisdictional challenges, the validity of digital evidence, and the balance between moral enforcement and human rights. Using a qualitative normative-empirical approach through document analysis, case studies, and interviews, the findings reveal significant limitations, including restricted jurisdiction, the absence of clear standards for digital evidence, and tensions between religious norms and individual freedoms. The study emphasizes the need for legal reform, institutional coordination, and technological integration to ensure that Syariah law remains effective, relevant, and aligned with principles of justice and human rights in the digital era.